Room temperature chemiresistive gas sensors: challenges and strategies—a mini review - Srinivasan, Parthasarathy; Ezhilan, Madeshwari; Kulandaisamy, Arockia Jayalatha; Babu, K. Jayanth; Rayappan, John Bosco Balaguru (Journal of materials science. Materials in electronics, 2019)
One of the sources of environmental threat in recent years is the leakage of toxic gases from various industries. Sensors to detect these gases in trace level concentrations are highly required to ensure a safe living environment. In this context, many types of gas sensors such as calorimetric, conductometric, potentiometric, catalytic, and chemiresistive types have been employed to detect these gases. Among them, chemiresistive type sensors have been widely employed due to high selectivity, sensitivity, simplicity in fabrication, compactness, lower operating temperature, and low power consumption. Chemiresistive sensors are designed with inbuilt micro-heaters for improving the sensing response. However, sensors operated at elevated operating temperatures would significantly affect the stability of the sensor due to grain growth. To address this concern, many efforts have been progressing over the years towards the development of room temperature operated gas sensors. In this review, room temperature operated gas sensors developed for the detection of ammonia, acetaldehyde, ethanol, nitrogen dioxide, ozone, and aromatic VOCs have been discussed. In addition, the major challenges possessed by the sensors operated at elevated temperatures such as grain growth, change of conductivity, and variations in charge transport characteristics have been addressed. Also, the strategies to minimize the aforementioned challenges have been highlighted.